Enhanced aerodynamic performance of NACA 0009 morphing airfoil: a study on camber morphing and vortex generators - Dol, Sharul Sham; Pagaling, Joaquin Rafael; Almansoori, Dana; Hamdan, Hasan (Penerbit Akademia Baru, 2025)
This study investigates the aerodynamic benefits of adaptive morphing airfoil that include camber morphing with vortex generators, focusing on their impacts on lift, drag and flow management. It involves CFD simulations of a NACA 0009 airfoil were performed on four methods: uncambered without vortex generators, uncambered with vortex generators, cambered without vortex generators and cambered with vortex generators; additionally, these simulations analysed lift-to-drag ratios, boundary layer stability and flow separation across a range of angles of attack (AOA). The results clearly demonstrate the good performance of the cambered airfoil with vortex generators, which had the highest lift-to-drag ratio, delayed flow separation and greatly improved boundary layer stability, particularly at higher angles of attack. Furthermore, the CFD simulations were highly supported by the flow visualization results, which demonstrated a strong link between wake generation, flow separation patterns and pressure distribution. At increasing angles of attack, the observed start of stall and wake turbulence closely matched the simulation findings, confirming the accuracy of the results. Nonetheless, camber morphing improved flow circulation around the airfoil, resulting in more lift generation, while vortex generators stimulated the boundary layer, thereby delaying separation and decreasing drag. This study underlines the significance of combining camber morphing and vortex generators into airfoil designs, offering a transformative approach to addressing critical issues in modern aviation, such as fuel efficiency and operational flexibility; finally, the findings provide a solid platform for future developments in morphing airfoil technology and its practical application in aerospace engineering.